2023
DOI: 10.1590/1517-8692202329012022_0187
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Interventions of Common Sports Injuries in College Basketball Players

Abstract: Introduction As college basketball continues to develop, more and more college students are joining the sport, and the resulting sports injuries have also gradually increased, affecting the quality of life and academic performance. Objective Analyze the most common sports injuries and offer solutions for the safe practice of college basketball. Methods This article studies, through interviews and literature review, the basketball injuries of college students, analyze the main causes of sports injuries, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Some researchers have focused on the injuries caused by basketball training and sports among students in vocational colleges and physical education colleges (Makovicka et al,2019). Through on-site questionnaire surveys and data statistical analysis, it has been found that the main reasons for student injuries are insufficient self-protection measures, insufficient warm-up preparations in the early stages of sports, slippery ground conditions, and physical conditions at the time (Zhang, 2022). Corresponding preventive measures have been proposed based on these reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have focused on the injuries caused by basketball training and sports among students in vocational colleges and physical education colleges (Makovicka et al,2019). Through on-site questionnaire surveys and data statistical analysis, it has been found that the main reasons for student injuries are insufficient self-protection measures, insufficient warm-up preparations in the early stages of sports, slippery ground conditions, and physical conditions at the time (Zhang, 2022). Corresponding preventive measures have been proposed based on these reasons.…”
Section: Introductionmentioning
confidence: 99%